2004
DOI: 10.1023/b:aibe.0000030245.52406.bb
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Medication Adherence Beliefs and Self-Efficacy in Persons Naive to Antiretroviral Therapy: A Multicenter, Cross-Sectional Study

Abstract: It is widely recognized that adherence to antiretroviral therapy is critical to long-term treatment success, yet rates of adherence to antiretroviral medications are frequently subtherapeutic. Beliefs about antiretroviral therapy and psychosocial characteristics of HIV-positive persons naive to therapy may influence early experience with antiretroviral medication adherence and therefore could be important when designing programs to improve adherence to antiretroviral therapy. As part of a multicenter AIDS Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
122
2
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 30 publications
9
122
2
7
Order By: Relevance
“…Beliefs about illness and medicines have been widely researched in chronic disease, [29][30][31][32] but not until recently in glaucoma. A cross-sectional survey of glaucoma patients, which incorporated the Brief IPQ 33 and the BMQ, 18 found as we did that patients with poor adherence had more concerns and less belief in the necessity of drops.…”
Section: Discussionmentioning
confidence: 99%
“…Beliefs about illness and medicines have been widely researched in chronic disease, [29][30][31][32] but not until recently in glaucoma. A cross-sectional survey of glaucoma patients, which incorporated the Brief IPQ 33 and the BMQ, 18 found as we did that patients with poor adherence had more concerns and less belief in the necessity of drops.…”
Section: Discussionmentioning
confidence: 99%
“…Community members may not seek VCT because of the fear of discovering that they are HIV positive and fear of the resulting stigma and discrimination that may accompany their HIV/AIDS positive status. Thus, HIV/AIDS related stigma and discrimination may have a profound impact on the disclosure (revelation) of HIV status and the subsequent care, support, or treatment that HIV positive persons receive , Muyinda, et al 1997, Weiss and Ramakrishna 2001, Mill 2003, Carr and Gramling 2004, Reynolds, et al 2004. In Ghana, HIV positive persons hide their HIV-seropositive status to reduce HIV/AIDS related stigma and discrimination and to retain the care and support of family members.…”
Section: Introductionmentioning
confidence: 99%
“…Ironically, this secrecy hinders uptake of treatment and of support services that can be provided by family members (Mill 2003). People who feel stigmatized or discriminated against are more likely to have poor health outcomes, socio-psychological problems, and suicidal thoughts , Reynolds, et al 2004, Bottonari, et al 2005, Katz and Nevid 2005, Sledjeski, et al 2005. Tackling HIV stigma will involve tackling perceptions and values towards sexuality and HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Younger patients appear to live more active lifestyles and spend periods of time away from home, or are involved in different activities leading them to forget medication when out of their normal routine. Studies involving patients with chronic diseases, such as diabetes 51 and HIV, 52 found that poor adherence arose as patients had difficulties changing their lifestyle to integrate a therapeutic regimen. As we also found, forgetfulness is frequently cited as a reason for poor adherence 20,37,[53][54][55] ; an intervention incorporating reminder systems into daily activities may prove advantageous.…”
Section: Discussionmentioning
confidence: 99%